ANALISIS STRUKTUR SPASIAL JARINGAN JALAN PERKOTAAN: STUDI KASUS KOTA PONTIANAK - Wulandari, Agustiah; Purnomo, Yudi (Jurnal Spasial, 2025)
The structure of road networks plays a crucial role in supporting mobility, transportation efficiency, and urban spatial development. Pontianak City, as one of the growth centers in West Kalimantan, faces increasing challenges in managing its increasingly complex road network. This study aims to analyze the spatial structure of the urban road network in the central area of Pontianak using a spatial approach based on Geographic Information Systems (GIS) with QGIS software. The methods include identifying road network nodes, calculating total road length, and analyzing network density across two spatial units: 500 x 500meter grids and administrative boundaries at the kelurahan level. The analysis reveals that the distribution of the road network is uneven, with the highest concentration of road length and network nodes found in central areas such as Tengah and Akcaya Subdistricts. In contrast, the northern and eastern parts of the city exhibit sparser network structures. The grid-based approach provides greater spatial precision in capturing micro-scale variation, while the kelurahan units are relevant for policy and regional planning contexts. These findings form a basis for planning equitable, efficient, and data-driven road infrastructure development.